Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pemerintah Daerah Provinsi Jawa Tengah Tahun Anggaran 2019-2022 - Puspita Geatri Br Perangin-Angin; Erisma Adi Natalian; Risma Wira Bharata (Manajemen Kreatif Jurnal, 2023)
By doing this research aims to examine the financial performance of the local government of Central Java Province. This analysis uses regional financial independence ratios, financial efficiency ratios, PAD effectiveness ratios, and growth ratios to assess financial performance. This study is included in the category of quantitative descriptive research. The data used comes from the Financial Report of the Central Java Provincial Government for the 2019-2022 budget period. Financial ratio analysis is the method used to perform this analysis. As shown by the research results, the financial performance of the Central Java Provincial Government is still far from optimal. Regional Original Revenue Management has proven successful, but regional finances are still inefficient. In addition, the level of regional independence is still low, as shown by the increase in central government assistance compared to the regional original income of Central Java Province.